The use of eco-development programs for the assessment of environmental changes and the effectiveness of pro-ecological actions of local government administration at municipal level - Piotr Lewandowski; Piotr Zydlik (Economic and Environmental Studies (E&ES), 2016)
An analysis of environmental protection in 30 selected municipalities of the Greater Poland Province was performed. Municipal eco-development programmes developed in the years 1998-2013 were used for this purpose. Their analysis made it possible to conclude that the conditions of the environment have improved significantly in the area under analysis. The quality of air and surface waters has been improving, the length of the sewerage networks has been growing and the number of modernized or newly commissioned municipal sewage treatment plants. Among employees of local government administration the role and importance of ecological education has been growing significantly. It is still necessary to undertake greater efforts towards elimination of household coal-fired systems in municipalities and a rational municipal waste management policy. Among pro-ecological purposes to be achieved in eco-development programs, water and sewage management tasks, as well as preparation or updates of planning documents, including environmental inventories and valuation, are quite common.
Keywords: Q01; Q56; Q58; 330; sustainable development; municipal local government administration; pro-ecological investments; ecological education